Development of Execution Guidelines For Maintenance, Reparation, and Material Specification Determination of Green Building Landscape Component Work in Government Building Based on Work Breakdown Structure (WBS) - Anna Wahidati Rahmah (AIBPM Publisher, 2018)
In designing a construction project, it is early important to consider the purpose and benefit of it uses. Maintenance and reparation work are activities to maintain the function of the building to remain in accordance with the original purpose of the development. The purpose of this research is to establish an execution guidelines for landscape component based on Work Breakdown Structure (WBS). Execution guidelines is a parameter that become the basis rules that should be fulfilled by the designer. The research methodology covers several stages: literature studies and delphi techniques through expert. The results of this study are expected to create implementation guidelines for managing the maintenance and reparation work that can improve the effectiveness and efficiency of building maintenance. Keywords: Project Management, Work Breakdown Structure, Maintenance, Reparation, Specification Determination, Government Building, Green Building